EVALUASI KINERJA BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM MENCEGAH DAN MENANGGULANGI BENCANA ALAM DI KABUPATEN GRESIK TAHUN 2021 (Fakultas Ekonomi Universitas Wisnuwardhana, 2023)
This study aims to evaluate the performance of the Regional Disaster Management Agency in preventing and overcoming natural disasters in Gresik Regency in 2021. This study uses descriptive qualitative methods so that to support this research, it is carried out by collecting data from the field, after that it is reduced or summarized according to the information obtained, then displayed or presented the opinions of informants according to performance indicators from BPBD Gresik Regency, then tested the validity of the data. using source triangulation and member check. So it can be concluded that the achievement of BPBD productivity in Gresik Regency can be said to be good but not optimal. In providing services for disasters, BPBD still cooperates with other stakeholders. So that in the implementation of handling causes delays. Several times the Gresik Regency BPBD has also carried out disaster prevention and mitigation training. Responsively BPBD Gresik Regency has been good, quick and spontaneous in carrying out emergency actions to carry out rescue, search, rescue and health services as well as social services for disaster victims. In accountability, the Gresik Regency BPBD has been carried out in accordance with existing standards.